Morphological and immunohistochemical analysis of tumor-infiltrating lymphocytes, M2 macrophages, BCL 6 and SOX10 in the tumor microenvironment of nodular cutaneous melanoma - K. S. Titov; A. A. Markin; E. I. Schurygina; N. S. Karnaukhov; D. A. Zaryanov; D. N. Bubenko (Опухоли головы и шеи)
Introduction. Cutaneous melanoma is one of the most aggressive malignant tumors, and its nodular form with vertical growth is characterized by unfavorable prognosis. However, in the recent years due to advances in basic oncology, a breakthrough in drug therapy of this pathology was made. To a great extent, it is linked to implementation of new therapy with checkpoint inhibitors. The best and longest response rates of cutaneous melanoma to this treatment were achieved compared to other oncological diseases. This fact can be explained by immunogenicity of cutaneous melanoma, high mutational load, as well as features of its tumor microenvironment, where in most cases high infiltration by immunocompetent cell is observed. However, immune cells vary by their composition and functions. Some of them can even promote tumor growth. Therefore, study of cell composition, degree and distribution of immune infiltration in the tumor can help identify potential factors of favorable and unfavorable prognosis for cutaneous melanoma which is important in clinical practice.Aim. To determine the frequency of CD3+-, CD4+-, CD8+-T-lymphocytes, CD163, BCL6 and SOX10 expression in patients with primary nodular cutaneous melanoma, as well as correlation of these markers with each other and standard morphological parameters for this non-epithelial malignant tumor.Materials and methods. In the study, the expression frequency of CD3+-, CD4+-, CD8+-T-lymphocytes, CD163, BCL6 and SOX10 in the postoperative material of 20 patients with true primary nodular cutaneous melanoma was measured using immunohistological analysis. The correlation of these markers with each other and standard morphological parameters was determined.Results. In most cases of nodular cutaneous melanoma, moderate and marked lymphocytic (immune) infiltration (grade II–III) was observed with no correlation with Breslow tumor thickness. Study of the ratio between CD4-positive T helpers and CD8-positive cytotoxic T lymphocytes in the tumor microenvironment showed that the number of the latter increased the higher was the degree of immune infiltrate. Markedness of macrophage infiltration directly correlated with markedness of lymphocytic infiltration. BCL6 expression in lymphocytes was observed in all cases of infiltration.Conclusion. Immune infiltrate in nodular cutaneous melanoma is a multicomponent, dynamic microenvironment containing both antitumor and tumor-promoting components with balance shifting to one or other side. Their qualitative, quantitative and, possibly, topographic ratios in the primary lesion of cutaneous melanoma affect the effectiveness of drugs and disease prognosis. Knowledge on the predominance of components negatively affecting tumor growth in the primary lesion can help an oncologist in selection of correct treatment tactics and disease observation.